AB0161 Investigation of Oxidative Stress, Oxygenation and Erythema in Patients with Systemic Sclerosis, Primary Raynaud's Phenomenon and Undifferentiated Connective Tissue Disease and in Healthy Controls. (15th July 2016) - Poxon, I.; Moore, T.L.; Manning, J.B.; Leggett, S.; Dickinson, M.; Herrick, A.L.; Murray, A.K.
Abstract : Background: Systemic sclerosis (SSc) is a rare connective tissue disease characterised by skin fibrosis and microvascular dysfunction. Oxidative stress, hypoxia and ischaemia have previously been implicated in SSc pathogenesis. Objectives: The aim of this study was to further elucidate the pathophysiology of different subtypes of Raynaud's phenomenon (RP) by measuring oxidative stress, oxygenation and perfusion in patients with primary RP (PRP), undifferentiated connective tissue disease (UCTD), and SSc, comparing between groups and with healthy controls. Patients with UCTD were included to understand more about their early structural and functional changes as they are potentially an interim group between PRP and SSc. Our hypothesis was that oxidative stress would be increased in the UCTD and SSc groups and the oxygenation and perfusion would be decreased. Methods: Measurements of oxidative stress, oxygenation and erythema (skin redness, an approximate, indirect measure of perfusion) were taken at a single point, at 9 sites, over the body using spectroscopy. Oxidative stress was measured as an increase in fluorescence induced by UV light. Oxygenation and erythema were calculated from white light reflection spectra. Results: Measurements were taken from 53 healthy controls (HC), 36 female (f), median age 45, IQR [38–54] years; 20 patients with PRP, 17 f, 46 [39–52] years, duration of RP 8 [3–25] years; 37 patients with UCTD, 26 f, 43 [31–54] years, duration of RP 7 [5–16] years; 100 patients with SSc, 83 f, 59 [52–66] years, duration of RP 16 [8–24] years, duration of SSc 11 [4–18] years. A subset of data over the 9 sites is shown in Table 1 . Oxidative stress was increased at all sites (statistically significant differences between groups [p<0.05] at 7/9 sites) in patients with SSc as compared to HC. Oxygenation showed no trend. Erythema showed a trend of lower values at all sites for patients with SSc vs. HC (statistically significant at 7/9 sites). Conclusions: Patients with SSc showed a trend towards increased oxidative stress and decreased erythema compared to HC as hypothesised, providing further evidence that both oxidative stress and ischaemia are associated with SSc. Oxygenation showed no trend, suggesting that oxygenation measurements may not be sensitive enough to detect differences or that oxygenation is not affected at baseline (i.e. it is functional rather than structural). Further studies may clarify whether incorporating a dynamic challenge (e.g. temperature change) would aid differentiation between groups. Acknowledgement: Arthritis Research UK and EPSRC funded this study. Disclosure of Interest: None declared